2011
DOI: 10.1101/lm.2175811
|View full text |Cite
|
Sign up to set email alerts
|

Extinction after retrieval: Effects on the associative and nonassociative components of remote contextual fear memory

Abstract: Long-lasting memories of adverse experiences are essential for individuals' survival but are also involved, in the form of recurrent recollections of the traumatic experience, in the aetiology of anxiety diseases (e.g., post-traumatic stress disorder [PTSD]). Extinction-based erasure of fear memories has long been pursued as a behavioral way to treat anxiety disorders; yet, such a procedure turns out to be transient, context-dependent, and ineffective unless it is applied immediately after trauma. Recent evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 78 publications
8
88
3
Order By: Relevance
“…These findings are consistent with those indicating that extinction shortly after fear learning or fear cue exposure impairs extinction and exacerbates spontaneous recovery, renewal, and reinstatement (Morris et al 2005;Chan et al 2010;Costanzi et al 2011;Ishii et al 2012). Other studies have found opposing results-that extinction soon after acquisition (Myers et al 2006) or retrieval (Monfils et al 2009) promotes the retention of extinction (see Flavell et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…These findings are consistent with those indicating that extinction shortly after fear learning or fear cue exposure impairs extinction and exacerbates spontaneous recovery, renewal, and reinstatement (Morris et al 2005;Chan et al 2010;Costanzi et al 2011;Ishii et al 2012). Other studies have found opposing results-that extinction soon after acquisition (Myers et al 2006) or retrieval (Monfils et al 2009) promotes the retention of extinction (see Flavell et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…When further extinction trials began 10 min later, the resulting extinction was much more durable and profound than when the extinction began 6 h later. Thus, although some studies report difficulties in reproducing Monfils's results (Chan et al 2010;Costanzi et al 2011), these findings by Monfils and Schiller suggest promising possibilities for therapeutic treatments for fear and anxiety. The research indicates that memory reactivation is necessary, but because of floor effects due to extinction itself, the work is not able to provide information about the length of time required for the integration of the extinction information within the memory trace.…”
Section: Reactivation Allows the Integration Of New Informationmentioning
confidence: 90%
“…Based on previous similar studies in fear conditioning procedures (eg, Liu et al, 2014;Monfils et al, 2009), it has been postulated that extinction training performed within the 'reconsolidation window' leads to incorporation of the new information (cue-nothing association) into the original cuereinforcement memory trace (eg, cue-drug) (Millan et al, 2013;Monfils et al, 2009;Sartor and Aston-Jones, 2014;Xue et al, 2012), rather than creating a competing memory as in regular extinction (Bouton, 2002;Milton and Everitt, 2012). However, several studies on fear memories showed that postretrieval extinction did not always prevent reinstatement of fear behavior (Chan et al, 2010;Costanzi et al, 2011;Ishii et al, 2015;Soeter and Kindt, 2011), and studies on drug relapse showed attenuation, but not always prevention of relapse to drug seeking (Luo et al, 2015;Xue et al, 2012). Comparative studies have indicated that counterconditioning may have a stronger suppressive effect on relapse of memories, compared with extinction (Tunstall et al, 2012;Van Gucht et al, 2010).…”
Section: Discussionmentioning
confidence: 99%